Adobe Photoshop Lightroom 3 video workshop library module, workflow, and photo library management - Jardine, George; Safari eBooks ([S.l.] : Peachpit Press, 2010)
"This set of 16 all-new video tutorials gives you over 4-1/2 hours of the very best online education available. It covers the Adobe Photoshop Lightroom 3 Library module and your digital photo library management from top to bottom. We start from the ground up and guide any serious photographer--professional or passionate amateur--through the process of building an easy-to-use but incredibly effective digital photo library. Then we dive deeper, tutorial-by-tutorial, through nearly every Lightroom Library feature, gently leading you to a solid and complete understanding of the entire professional workflow. Watch this video series and you will find thousands of tips and techniques that help you master your photo library and the new Lightroom 3 workflow"--Resource description page.
Photo library structure -- The Lightroom catalog overview -- The Lightroom user interface -- The pro workflow overview -- The Lightroom import dialog -- The library module - Part 1 -- The Library Module - Part 2 -- Keywords & metadata -- File renaming -- Editing methods in Lightroom 3 -- The Lightroom filter bar -- Virtual copies -- The export dialog & publish services -- The Lightroom-to-Photoshop workflow -- Digital photo library backup strategies -- Working with multiple Lightroom catalogs.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed Nov. 9, 2010).
Keywords: Adobe Photoshop lightroom; Photography -- Digital techniques -- Computer programs; Image processing -- Digital techniques -- Computer programs; Electronic books